Antibody responses to Chlamydia trachomatis vaccine candidate antigens in Chlamydia-infected women and correlation with antibody-mediated phagocytosis of elementary bodies - Yu, Hong; Geisler, William M.; Dai, Chuanbin; Gupta, Kanupriya; Cutter, Gary; Brunham, Robert C. (Frontiers in Cellular and Infection Microbiology, 2024)
Chlamydia reinfection. To explore potential humoral immune markers of protection elicited by Chlamydia trachomatis (CT) antigens in humans in the context of presumed clinical correlates of protection, we used both an IgG1-based ELISA and a conventional total IgG ELISA to evaluate antibody responses. We evaluated responses to five CT outer membrane proteins (PmpE, PmpF, PmpG, PmpH, and MOMP), along with other promising CT antigens (Pgp3 and HSP60), negative control antigens (RecO and AtpE), and CT elementary bodies (EBs) in sera from a well-characterized cohort of 60 women with different CT infection outcomes, including two outcomes that are likely clinical correlates of protective immunity: spontaneous resolution of infection and absence of reinfection after treatment. Furthermore, we used a flow cytometry-based assay to measure antibody-mediated phagocytosis by neutrophils in these sera. Results demonstrated that IgG1 ELISA displayed higher sensitivity than conventional total IgG ELISA in assessing antibody responses to CT EBs and antigens. Pgp3 IgG1 ELISA exhibited the highest sensitivity compared to IgG1 ELISA incorporating CT EBs or other antigens, confirming Pgp3 IgG1 ELISA as an ideal assay for CT antibody detection. Most (95%) sera from women with CT infection outcomes exhibited antibody-mediated phagocytosis of CT EBs, which was significantly correlated with IgG1 antibody responses to MOMP, Pgp3, HSP60, and PmpF. However, neither IgG1 responses to CT antigens and EBs nor antibody-mediated phagocytosis were associated with clinical correlates of protection. These findings suggest that neither CT IgG1 antibody detection nor antibody-mediated phagocytosis will be useful as immune correlates of protection against CT infection in humans.